Cross-sectional and longitudinal associations between physical activity, sedentary behaviour and bone stiffness index across weight status in European children and adolescents - Lan Cheng; Hermann Pohlabeln; Wolfgang Ahrens; Fabio Lauria; Toomas Veidebaum; Charalambos Chadjigeorgiou; Dénes Molnár; Gabriele Eiben; Nathalie Michels; Luis A. Moreno; Angie S. Page; Yannis Pitsiladis; et al. (BMC, 2020)
Abstract Background The associations between physical activity (PA), sedentary behaviour (SB) and bone health may be differentially affected by weight status during growth. This study aims to assess the cross-sectional and longitudinal associations between PA, SB and bone stiffness index (SI) in European children and adolescents, taking the weight status into consideration. Methods Calcaneus SI was first measured by quantitative ultrasound among children aged 2-9 years old in 2007/08. It was measured again after 2 years in the IDEFICS study and after 6 years in the I. Family study. A sample of 2008 participants with time spent at sports clubs, watching TV and playing computer/games self-reported by questionnaire, and a subsample of 1037 participants with SB, light PA (LPA) and moderate-to-vigorous PA (MVPA) objectively measured using Actigraph accelerometers were included in the analyses. Weight status was defined as thin/normal and overweight/obese according to the extended International Obesity Task Force criteria. Linear mixed-effects models were used to estimate the cross-sectional and longitudinal associations between PA, SB and SI percentiles, stratified by weight status. Results The cross-sectional association between weekly duration of watching TV and SI percentiles was negative in thin/normal weight group (β = − 0.35, p = 0.008). However, baseline weekly duration of watching TV (β = − 0.63, p = 0.021) and change after 2 years (β = − 0.63, p = 0.022) as well as the change in weekly duration of playing computer/games after 6 years (β = − 0.75, p = 0.019) were inversely associated with corresponding changes in SI percentiles in overweight/obese group. Change in time spent at sports clubs was positively associated with change in SI percentiles after 2 years (β = 1.28, p = 0.001), with comparable effect sizes across weight status. In the subsample with accelerometer data, we found a positive cross-sectional association between MVPA and SI percentiles in thin/normal weight group. Baseline MVPA predicted changes in SI percentiles after 2 and 6 years in all groups. Conclusions Our results suggested the beneficial effect of PA on SI. However, the increasing durations of screen-based SB might be risk factors for SI development, especially in overweight/obese children and adolescents.